1980
DOI: 10.1002/ajmg.1320050206
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling dilemmas: Down syndrome, paternal age, and recurrence risk after remarriage

Abstract: The recent demonstration that about 20&30%of cases of Down syndrome are of paternal origin has again raised interest in the question of the possible contribution of paternal age independent of matcrnal age to a couple's risk of a Down syndrome live birth. In this paper the nature of the available evidence is critically reviewed, interpretations reconciling differences between studies that reached opposite conclusions are presented, and an approach t o genetic counseling in the face of such apparent differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Advanced paternal age has been suggested to be a risk factor for an adverse pregnancy outcome (stillbirth, preterm birth and low birthweight), for structural anomalies (encephalocele and microcephalia, cleft lip and palate, neural tube defects and cardiac defects) and for some childhood disorders (autism spectrum disorder, schizophrenia or cancer) [5][6][7][8][9][10]. Regarding chromosomal anomalies, most of de novo structural aberrations are paternal in origin, in contrast to aneuploidies that are mainly of maternal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced paternal age has been suggested to be a risk factor for an adverse pregnancy outcome (stillbirth, preterm birth and low birthweight), for structural anomalies (encephalocele and microcephalia, cleft lip and palate, neural tube defects and cardiac defects) and for some childhood disorders (autism spectrum disorder, schizophrenia or cancer) [5][6][7][8][9][10]. Regarding chromosomal anomalies, most of de novo structural aberrations are paternal in origin, in contrast to aneuploidies that are mainly of maternal origin.…”
Section: Introductionmentioning
confidence: 99%
“…Hook (1980Hook ( , 1981 concluded that the then available literature suggested a doubling of risk for men over 55, but no effect for younger men. Stene,et al (198la) analyzed parental ages of 65 cases of trisomy 21 that were found among amniocenteses of women who were 35 or older.…”
Section: Criticizedmentioning
confidence: 99%